Designing the smart shopping cart mobile application (SmartCart) using mobile application development life cycle - Roslan, Muhammad Amirul Asyraaf; Haron, Haryani (Modern Education and Computer Science Press, 2024)
The primary objective of this paper is to design a SmartCart mobile application. The proposal centres around designing a mobile app that allows customers to engage in collaborative shopping with their family members or friends, effectively shopping together in a group. This project seeks to improve upon existing shopping mobile apps that predominantly focus on online shopping. Through the development of the SmartCart mobile application, users will have the capability to shop in physical stores while collaborating with others or their group. The application adheres to the Mobile Application Development Life Cycle (MADLC) methodology, focusing on the phases of identification, design, development, prototyping, and testing. This paper provides an in-depth description of each step within the methodology, commencing with the identification stage and culminating in the testing phase. To evaluate the application's usability, ten users from various backgrounds took part in the testing process, and their feedback, measured through the System Usability Scale (SUS), indicated a positive reception of the application. The paper presents the initial framework and design concept that preceded the development of the final SmartCart mobile application design. From a pool of around 50 paper prototypes, 18 were selected as pertinent and fitting for advancement to the subsequent stage. In this subsequent phase, the chosen designs were transformed into a medium-fidelity prototype before progressing to the actual development of the SmartCart mobile application. This paper fulfils an identified need to study how collaborative shopping mobile applications can be developed and prototyped.